Effect of Groove Shape in GTAW Welding on Bending Strength of Aluminium 6061 - Zulkarnain, Akbar; Tyas Damayanti, Ajeng; Yanuar Saputro, Roni (SAINSTECH NUSANTARA, 2024)
The Aluminum alloy 6061 material is used to make components for light trains such as underframes, sidewalls, roofs, and endwalls. A joining process called welding is used to make train components. In the connection process using welding, many stages must be considered, such as the design stage starting from selecting the type of welding, to choosing the seam angle used. This research aims to determine the effect of the shape of the seam on GTAW welding on bending tests on aluminum alloy 6061 material. The shape of the seam used in this research is a variation of the shape of the seam square groove, V groove, and double V groove. The research method used is research by conducting tests, based on the treatment given to the test material, namely welding using GTAW welding on aluminum alloy 6061. To determine the strength of the joint, bending tests are carried out, and calculation of the bending strength and modulus of elasticity value so that the shape of the joint can be determined. Has a high elasticity value. After welding and bending tests were carried out, the highest average bending strength result was 94.83 MPa in the double V groove seam shape variation, and for the specimen that had the lowest bending strength it was 41.299 MPa in the square groove seam shape variation. The elastic modulus calculation was carried out showing that the largest elastic modulus value in the Double V groove seam shape was 295.929 MPa.